Unusual bacteria causing peritonitis in peritoneal dialysis: A single centre experience - Farinha,Ana (2013)
Background:Peritonitis is one of the most common complications of peritoneal dialysis. The most frequent agents have been largely described and studied but unusual microorganisms have only been reported in case reports. Methods: We describe the cases of unusual bacteria causing peritonitis in our peritoneal dialysis patients between 1998 and 2012. Results: In this 15-year period, we have registered 188 peritonitis in 118 patients (0.64 episodes/patient/year). Unusual bacteria were considered all that have caused peritonitis in only one or two instances (12 bacteria in 15 episodes). We have performed antibiogram-based antibiotic therapy in all of them. In two cases catheter removal was necessary and one patient has died in direct relation with the peritonitis. Conclusions: Unusual bacterial agents may cause peritonitis in peritoneal dialysis. They are rare and may present with a broad spectrum of seriousness. Publication of experiences may help guiding therapy and increases scientific evidence